2017
DOI: 10.4103/2152-7806.198728
|View full text |Cite
|
Sign up to set email alerts
|

Parasagittal meningiomas: Our surgical experience and the reconstruction technique of the superior sagittal sinus

Abstract: Background:The radical resection of parasagittal meningiomas without complications and recurrences is the goal of the neurosurgeon. Nowadays, different managements are proposed. This study describes our surgical technique during the lesional excision and the reconstruction of the superior sagittal sinus (SSS).Methods:The total removal (Simpson I and II) of parasagittal meningiomas (WHO grade I and II) was obtained in 75 patients from September 2000 to January 2010. The indocyanine green videoangiography was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…However, the resulting prognostic factors of parasagital meningioma recurrence/continued growth in this study are consistent with the data from known literature sources (Behzadmehr et al, 2021, Balik et al, 2020, Cucu et al, 2020, Salah et al, 2019, Siempis et al, 2020. However, we found that recurrence-free 5-and 10-year survival in PM patients is as follows: 1) in case of total tumor removal (Simpson I), 96.0% and 85.5%, respectively; in case of non-radical removal (Simpson II-V), 88.9% (p<0.05) and 81.9% (p<0.05), respectively.…”
Section: Ukrainian Scientific Medical Youth Journalsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the resulting prognostic factors of parasagital meningioma recurrence/continued growth in this study are consistent with the data from known literature sources (Behzadmehr et al, 2021, Balik et al, 2020, Cucu et al, 2020, Salah et al, 2019, Siempis et al, 2020. However, we found that recurrence-free 5-and 10-year survival in PM patients is as follows: 1) in case of total tumor removal (Simpson I), 96.0% and 85.5%, respectively; in case of non-radical removal (Simpson II-V), 88.9% (p<0.05) and 81.9% (p<0.05), respectively.…”
Section: Ukrainian Scientific Medical Youth Journalsupporting
confidence: 92%
“…Sindou and J.E. Alvernia classification (types I-VI) (Ricci et al, 2017). The risk of parasagital meningioma recurrence was individually assessed in patients with types I-II, III-IV, and V-VI superior sagittal sinus damage according to M.P.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation